Electrochemical synthesis of self-organized TiO2 nanotubular structures using an ionic liquid (BMIM-BF4) - Paramasivam, Indhumati; Macák, Jan; Selvam, T.; Schmuki, Patrik (Electrochimica Acta, 2008)
We show that an ionic liquid consisting of imidazolium salt with a BF_4 counter ion (BMIM-BF_4) can directly be used to grow well-defined layers of self-organized TiO_2 nanotubes. For this a Ti metal substrate is anodized in this electrolyte for potential range between 3 VAg/AgCl and 10 VAg/AgCl without addition of free fluoride species (fluorides are used in all previous tube growth procedures). Key factors that influence the morphology and geometry of the resulting nanotubular layer are the anodic potential, the anodization time and particularly the water content in the ionic liquid. The resulting nanotubes layers have thickness in the range of approximately 300–650 nm; with individual tubes that have diameters between 27 nm and 43 nm.
EAM Import::2019-03-14